Knowledge Transfer from Veteran Seafarers to Maritime Cadets Through Mentorship-Based Education - Purnama, Chanra; Cahyadi, Tri; Faozun, Irfan; Barasa, Larsen; Hidayat, Benny; Utama, Yusuf Pria (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This qualitative study develops and evaluates a mentorship-based educational model designed to facilitate the transfer of occupational health and safety knowledge from veteran seafarers to maritime cadets in Indonesian maritime vocational institutions. While maritime graduates receive comprehensive technical training aligned with Standards of Training, Certification and Watchkeeping for Seafarers (STCW) standards, they often report feeling unprepared for the health and safety challenges they face at sea, indicating significant gaps in experiential knowledge transfer. The study conducted interviews with 20 veteran seafarers, 12 maritime lecturers, and 15 cadets, alongside a pilot implementation across three BPSDMP institutions. The findings identify key tacit knowledge areas that are insufficiently addressed in current curricula, particularly in practical emergency response adaptation (100% stakeholder recognition), fatigue self-management (94.7%), and psychological coping strategies (91.5%). The research reveals strong support for structured mentorship programs, emphasizing one-on-one relationships (100% cadet endorsement), post-graduation continuation (100% lecturer/cadet support), and weekly digital communication (100%). However, the successful implementation of these programs requires significant professional development for lecturers to facilitate mentorship roles (2.0-point capacity gap), formal institutional policies to legitimize mentorship, and preparation for veterans in pedagogical techniques. Pilot results demonstrate the feasibility of this model across diverse contexts, with high cadet knowledge gains (4.4/5.0 average) and veteran satisfaction (4.6/5.0), though variations across institutions highlight enabling conditions that influence outcomes. This study provides evidence-based implementation guidelines for BPSDMP institutions, offering a roadmap for integrating veteran experiential wisdom into maritime education, with implications for improving both the technical competence and resilience of future maritime professionals.